322 Challenges for porc value chains - simultaneous implementation of elevated animal welfare standards under field conditions. (5th December 2019) - Steinhoff-Wagner, Julia; Meier, Neele; Diel, Maria; Dynowski, Kamila; Heinemann, Celine; Stein, Jonas; Bode, Christian; Meyer, Isabell; Dieckhoff, Benedikt G Schulze; Bleeser, Ramona; Hayer, Jason J; Erdmann, Sandra
Abstract: Consumers increasingly demand an improvement of animal welfare, in particular a refrainment from surgical interventions such as tail docking and castration. The aim of the study was to investigate effects of simultaneous implementation of elevated welfare standards under field conditions on valid indicators at the abattoir and product quality. Six different pig farms from birth to fattening were reimbursed for implementing elevated welfare standards (no tail docking in all and no castration of male piglets). Farmers were free to try Improvac® treatments and boar fattening. At the abattoir, welfare indicators like swellings and conditions of ears, claws, skin and tails were inspected on carcasses (pigs: n >1866). Meat quality was evaluated (n >185). Fixed effects of sex (females and barrows, Improvac® treated boars, boars) and farm were included in mixed models and Pearson correlations were calculated (SAS 9.4). Results were condensed with a Failure Mode and Effects Analysis (FMEA). Two farms managed to deliver around 90% of pigs with intact tails, whereas one completely failed (80% tails shorter than 1/3 of original length). Sex affected almost all welfare indicators, with least impairments in the females and barrows group and most in boars (P < 0.01). FMEA revealed concerns regarding animal welfare and meat quality in boars and immense variation between farms. For example, drip losses showed an interaction between sex and farm, suggesting that some farms provide better conditions for Improvac® treated pigs and boars than others. Besides that, transport duration from fattening location to abattoir correlated with swelling on fore and hind legs (0.15< r< 0.17; P < 0.001), but did not affect tail classification. In conclusion, the implementation of elevated animal welfare standards was highly dependent on the farm-specific management. Because used indicators were successfully assessed on the carcasses, they seem to be valid for future reward systems.